FOREIGN EXCHANGE RATE AND INTERNATIONAL TRADE: A CASE OF INDONESIA IN OCTOBER 2023 - Ramadhan, Muhammad Rheza; Arifandi, Budi (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2024)
The weakening of the rupiah exchange rate, especially at the end of 2023, is mainly caused by global factors such as the increase in interest rates by the Fed, conflicts in Ukraine and the Middle East, and the strengthening of the US economy. Based on empirical data in 2017-2022, the relationship between the rupiah exchange rate against the USD and the volume of exports and imports is positive. Thus, the depreciation of the rupiah exchange rate increases the volume of exports and imports simultaneously. This is due to the close relationship between the value of exports and the value of imports, one of which is caused by the proportion of raw material imports which reaches 75% of the total import value. In addition, it is also caused by many other factors besides the rupiah value that affect imports and exports. The decline in the rupiah exchange rate is predicted to continue until 2024 given the predictions of the US economy that continues to increase and the increase in interest rates by the Fed. Although, the rupiah is predicted to reach a level of IDR 16,000/USD, Indonesia's foreign exchange reserves are indicated to continue to be at a safe level as assuming imports and external debt do not change significantly, the foreign exchange reserves would need to shrink to below USD 67.45 to bring Indonesia to an unsafe point. The weakening of the rupiah, which is expected to continue until 2024, will also increase inflation.